Independent monetary policy in a very open economy : challenges, costs and benefits - Robinson, John W. (1999)
Reviews the options that were open to policy-makers in the choice of exchange rate regime, and the implications of each of the choices made across the region. Sets out the conceptual and operational framework used in the process of formulating monetary policy and the way it was used to deal flexibly with challenges from capital flows, fiscal impulses and real shocks in Jamaica. Assess the nature of the costs - interest costs, reserve accumulation, financial restructuring - and looks at ways to minimise these over the medium-term.